Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ajt.15129
|View full text |Cite
|
Sign up to set email alerts
|

Organ procurement center allows for daytime liver transplantation with less resource utilization: May address burnout, pipeline, and safety for field of transplantation

Abstract: Abdominal organ transplantation faces several challenges: burnout, limited pipeline of future surgeons, changes in liver allocation potentially impacting organ procurement travel, and travel safety. The organ procurement center (OPC) model may be one way to mitigate these issues. Liver transplants from 2009 to 2016 were reviewed.There were 755 liver transplants performed with 525 OPC and 230 in-hospital procurements. The majority of transplants (87.4%) were started during daytime hours (5 am-7 pm). Transplants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…One proposed reason may be financial hardship associated with child care on a fellow salary. Jesse et al found that difficulties with flexible childcare lead to higher rates of EE among transplant attendings 27 . The demands of a transplant fellowship may magnify these difficulties, often leaving a spouse to function as a single parent.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed reason may be financial hardship associated with child care on a fellow salary. Jesse et al found that difficulties with flexible childcare lead to higher rates of EE among transplant attendings 27 . The demands of a transplant fellowship may magnify these difficulties, often leaving a spouse to function as a single parent.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chest CT may be a method of detecting poor quality or inappropriately sized lungs remotely, prior to sending a retrieval team to evaluate the organ. There is a substantial cost and risk to personnel associated with flying a retrieval team to evaluate organs [22], and improved methods of evaluating potential donors remotely are greatly needed.…”
Section: Discussionmentioning
confidence: 99%
“…We found that only 16% of our respondents utilized a recovery center during the past year and we believe this represents massive underutilization of a resource likely to drastically improve safety within the field. A very recent report by Lindemann et al 15 highlights further advantages of daytime-operating enabled by organ procurement centers including increased rates of extubation in the operating room and decreases in postoperative transfusion. The authors speculate that organ procurement centers will reduce transplant surgeon burnout and enhance recruitment of young surgeons into the field.…”
Section: Discussionmentioning
confidence: 99%